A new species of Alipumilio Shannon, 1927 (Diptera: Syrphidae), with the description of the male of A. avispas Vockeroth, 1964 and A. femoratus Shannon, 1927 - Parada-Marin, Henry Mauricio; Mengual, Ximo; Ramos-Pastrana, Yardany (Zootaxa, 2024)
Alipumilio Shannon, 1927 is a flower fly genus endemic to the New World, comprising five described species. In the present study we describe Alipumulio aureus sp. nov. from the Colombian Amazon region. This is the first record of this genus from Colombia. Additionally, the male of A. avispas Vockeroth, 1964 is described from Peru and the male of A. femoratus Shannon, 1927 is described from new material collected in Ecuador. Moreover, we provide an identification key to all the Alipumilio species and a species distribution map.